Managing biodiversity in agricultural ecosystems [Arabic version]: إدارة التنوع الحيوي في النظم البيئية الزراعية - Jarvis, Devra I.; Padoch, Christine; Cooper, H.D.; Bioversity International (2010)
إدارة التنوع الحيوي في النظم البيئية الزراعية Managing Biodiversity in Agricultural Ecosystems takes a look at how farmers manage, maintain, and benefit from biodiversity in agricultural production systems. The volume includes the most recent research and developments in the maintenance of local diversity at the genetic, species, and ecosystem levels. Chapters cover the assessment and farmer management practices for crop, livestock, aquatic, and associated diversity (such as pollinators and soil microorganisms) in agricultural ecosystems; examine the potential role of diversity in minimizing pest and disease pressures; and present studies that exemplify the potential nutritional, ecosystem-service, and financial values of this diversity under changing economic and environmental conditions. The volume contains perspectives that combine the thinking of social and biological scientists. Inappropriate or excessive use of inputs can cause damage to biodiversity within agricultural ecosystems and compromise future productivity. This book features numerous case studies that show how farmers have used alternative approaches to managing biodiversity to enhance the stability, resilience, and productivity of their farms, pointing the way toward improved biodiversity on a global scale. As custodians of the world's agricultural biodiversity, farmers are fully invested in ways to create, sustain, and assist in the evolution and adaptation of a variety of plant and animal species. Thus this text is mandatory reading for conservationists, environmentalists, botanists, zoologists, geneticists, and anyone interested in the health of our ecosystem. (Abstract © Columbia University Press / New York)